Post a New Question

Math - Limits

posted by .

What is the derivative of f(x) = 10 + sqrt(2x + 32)?

  • Math - Limits -

    very straightforward question

    f(x) = 10 + (2x+32)^(1/2)

    f ' (x) = (1/2)(2x+32)^(-1/2) * 2
    = 1/√(2x+32)

  • Math - Limits -

    Why is it multiplied by 2?

Respond to this Question

First Name
School Subject
Your Answer

Similar Questions

  1. calc

    find the derivative of y = sqrt(9 - 16x) Use the chain rule. First find the derivative of the sqrt, and multiply that by the derivative of what is contained inside. Cake. Use the chain rule. If we have y(x)=sqrt(9-16x) then y'=d/dx(sqrt(9-16x))*d/dx(9-16x) …
  2. CALCULUS 2!!! PLEASE HELP!!

    I'm having trouble with this question on arc length: y=lnx, (squareroot)3/3 greater than or equal to x less than or equal to 1 It sounds as if you want the length of the y = ln x curve from x = sqrt(3)/3 (0.57735..) to 1. The formula …
  3. Calculus

    find derivitive of 1/square root of x 1/square root of x = x^(-1/2) The derivative is -1/2 x^(-3/2) can you keep going on the problem to not have negative exponents?
  4. Math-Limits

    sqrt(1+tan x)-sqrt(1+sin x) lim all divided by x^3 x-->0
  5. Math Help please!!

    Could someone show me how to solve these problems step by step.... I am confused on how to fully break this down to simpliest terms sqrt 3 * sqrt 15= sqrt 6 * sqrt 8 = sqrt 20 * sqrt 5 = since both terms are sqrt , you can combine …
  6. Calculus

    Find the derivative of cos(sqrt(e^(x^3)cos(x)) I got -sin(sqrt(e^(x^3)cos(x))*((sqrt(e^(x^3)cos(x)) Do I just leave the e^(x^3)cosx alone since it's "e" or do I still have the find the derivative for it?
  7. Calculus

    derivative of ((Sqrt(x+3y)+sqrt(3xy))=(sqrt(21)+sqrt(90)) at point (6,5)google
  8. math/derivatives

    Please compute the derivative for g(x)= sqrt x - 3/x squared. I know the derivative for sqrt x = x ^1/2
  9. math please help!!

    For what values of x is the graph of y = 8e^−x^2 concave down?
  10. Calculus - Integrating

    Question: ∫(x^2)/sqrt(x^2+1) u=x^2+1 , x^2= u-1, du=2xdx ∫(u-1)/sqrt(u) , expand ∫u/sqrt(u) - 1/sqrt(u) Integrate: 2/3(u^(3/2)) - 2u^(1/2) + c My answer: [ 2/3(x^2+1)^(3/2) - 2(x^2+1) + c ] When I took the derivative of this …

More Similar Questions

Post a New Question